Cyclical Changes in Prolactin Levels among Infertile Women Attending University of Port Harcourt Teaching Hospital - Braide A Solomon; Adego O Adebayo; Bamigbowu E Olugbenga (Journal of Applied Sciences and Environmental Management)
Study was carried out to determine the effect of cyclical changes of prolactin concentrations on infertility in 3 groups of infertile subjects attending university of Port Harcourt teaching hospital for infertility treatments. Prolactin samples of the subjects were determined at follicular (day3), Midcycle (day14) and luteal phase (day21) using enzyme immune assay method (EIA). Prolactin was significantly increased in infertile subjects compared with the controls (Apparently fertile) suggesting an increase in prolactin concentration in infertile subjects. There was also cyclical changes observed in prolactin secretion with midcycle (day14) being the peak. Cyclical changes were also observed in prolactin concentration in both fertile and infertile subjects which peaked at midcycle (day14) suggesting that cycle of subjects should be taken into consideration in estimation, interpretation and investigation of infertility while the elevation of prolactin in the 3 study groups might be responsible for the infertility observed. @JASEM